A Feedback Model for Automated Real Estate Assessment - Carbone, Robert; Longini, Richard L. (Management Science, 1977)
Pressing changes are needed in the administration of real estate taxation that will not only ensure that all properties be assessed accurately and equitably, but will enable taxpayers to perceive that they are being treated fairly. In this paper, we examine what properties an automated mass appraisal system should exhibit so as to meet efficacy, equity and public acceptability criteria. A new automated system designed on the basis of these properties which utilizes feedback control and pattern recognition concepts is presented. Results of an empirical study using Pittsburgh data supports the feasibility of the proposed system.